Influence of the solution pH on the design of a hydro-mechanical magneto-hydraulic sealing device. (May 2022) - Li, Wangxu; Li, Zhenggui; Qin, Zhao; Yan, Shengnan; Wang, Ziyue; Peng, Shengyang
Highlights: Acidic and alkaline solution exhibited inhibitory effect against cavitation. Acidic solutions have higher inhibitory effect than alkaline solutions. The cavitation degree and flow length increased with higher deviation from pH = 7. The cycle period reduced with higher offset value from pH = 7. Acidic solutions should be used as reference for magneto-hydraulic sealing design. Abstract: Owing to the different pH values of water resources in different places, it is not practical to design hydraulic–mechanical magneto-hydraulic sealing devices under clean water conditions. This study used a Venturi structure to analyze the relationship between the solution pH and cavitation. A high-speed camera and turbine flowmeter were used to record the primary cavitation flow rate, shedding period of the cavitation cloud, and flow direction length of the cavitation cloud of solutions with different pH values. The results showed that acidic and alkaline solutions can inhibit the occurrence of primary cavitation. Compared with clean water, acidic and alkaline solutions have longer cavitation cloud flow length, shortened cavitation cycle, and higher degree of cavitation. In detail, the degree of cavitation in the acidic solution is stronger than that in the alkaline solution. Therefore, the amplitude of the pressure pulsation in an acidic solution should be taken as the reference when designing a hydro-mechanical magneto-hydraulic sealing device.